2022
DOI: 10.3389/fgene.2022.983525
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping and identification of candidate genes using a genome-wide association study for heat tolerance at anthesis in rice (Oryza sativa L.)

Abstract: Heat tolerance (HT) of rice at anthesis is a key trait that ensures high and stable yields under heat stress. Finding the quantitative trait loci (QTLs) and gene loci controlling HT is crucial. We used relative spikelet fertility (RSF) as a measure of HT. The phenotypic values of RSF in 173 rice accessions were investigated in two environments and showed abundant variations. We performed a genomewide association study on RSF using 1.2 million single nucleotide polymorphisms (SNPs). Five QTLs were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…We also observed important AS events in mitochondria-related genes. For example, LOC_Os09g38500.1 (cluster 2) codes for a mitochondrial glycoprotein, probably responsible for protecting the mitochondrial membrane system from HS damage ( Hu et al, 2022 ), while isoforms LOC_Os09g38500.2 and LOC_Os09g38500.3 have exon junction complexes > 50 nt downstream their stop codon, a frequent NMD-targeting feature ( Hug et al, 2016 ), meaning they might not be translated. We observed that these three transcripts switch in their relative proportions upon different exposure times to high temperatures ( Figure 2C ), suggesting that LOC_Os09g38500 splicing regulation can be crucial for HS responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed important AS events in mitochondria-related genes. For example, LOC_Os09g38500.1 (cluster 2) codes for a mitochondrial glycoprotein, probably responsible for protecting the mitochondrial membrane system from HS damage ( Hu et al, 2022 ), while isoforms LOC_Os09g38500.2 and LOC_Os09g38500.3 have exon junction complexes > 50 nt downstream their stop codon, a frequent NMD-targeting feature ( Hug et al, 2016 ), meaning they might not be translated. We observed that these three transcripts switch in their relative proportions upon different exposure times to high temperatures ( Figure 2C ), suggesting that LOC_Os09g38500 splicing regulation can be crucial for HS responses.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach considerably facilitated the discovery of previously unknown candidates involved in the HS response and expanded our knowledge of known heat-responsive genes. For example, Hu et al (2022) carried out a genome-wide association analysis that identified LOC_Os09g38500 as a candidate gene for thermotolerance. This gene is present in our network and we suggest that LOC_Os09g38500 splicing regulation ( Figure 2C ) can be crucial for HS responses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified five QTL associated with relative spikelet fertility (RSF) rate, one of which ( qRSF9.2 ) contained 16 candidate genes for HS tolerance (Hu et al, 2022). One specific gene ( LOC_Os09g38500 ) contained non‐synonymous SNPs significantly associated with RSF (Hu et al, 2022). A meta‐QTL analysis was conducted to identify potential candidate genes associated with the rice grain chalkiness trait, retrieving 64 meta‐QTL from a pool of 403 previously identified QTL comprising 5,262 non‐redundant genes (Kumar et al, 2023a).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%
“…Anthesis is a critical phase in the rice development cycle, significantly influencing grain yield and quality. A recent study identified five QTL associated with relative spikelet fertility (RSF) rate, one of which ( qRSF9.2 ) contained 16 candidate genes for HS tolerance (Hu et al, 2022). One specific gene ( LOC_Os09g38500 ) contained non‐synonymous SNPs significantly associated with RSF (Hu et al, 2022).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%
“…Hu et al used relative spikelet fertility as an index of heat tolerance and carried out genome-wide association analysis on the characters of 173 rice materials under two environments. Five significantly related QTLs were detected, of which a new QTL, qRSF9.2 , was located and its region narrowed to the 22,110,508–22,187,677 bp region on chromosome 9 [ 33 ]. There are similar heat-tolerant QTLs in rice, indicating that the metabolic pathway of heat tolerance among different rice varieties may be conservative, and some effective QTLs can be stably expressed.…”
Section: Qtl Identification Of Heat Tolerance In Ricementioning
confidence: 99%